2023
DOI: 10.3390/microorganisms11061516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy-Metal-Resistant PGPR Inoculants on Growth, Rhizosphere Microbiome and Remediation Potential of Miscanthus × giganteus in Zinc-Contaminated Soil

Abstract: Microbial-assisted phytoremediation is considered a more effective approach to soil rehabilitation than the sole use of plants. Mycolicibacterium sp. Pb113 and Chitinophaga sp. Zn19, heavy-metal-resistant PGPR strains originally isolated from the rhizosphere of Miscanthus × giganteus, were used as inoculants of the host plant grown in control and zinc-contaminated (1650 mg/kg) soil in a 4-month pot experiment. The diversity and taxonomic structure of the rhizosphere microbiomes, assessed with metagenomic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Many identified taxa are involved in Zn remediation in soils, including members of Bacillus , Sphingomonas , and Pseudomonas . 50 Similarly, Liu et al 51 observed increased Sphingomonas , Subgroup_7 , and Microscillaceae abundance after ZnO NP supplementation.…”
Section: Discussionmentioning
confidence: 92%
“…Many identified taxa are involved in Zn remediation in soils, including members of Bacillus , Sphingomonas , and Pseudomonas . 50 Similarly, Liu et al 51 observed increased Sphingomonas , Subgroup_7 , and Microscillaceae abundance after ZnO NP supplementation.…”
Section: Discussionmentioning
confidence: 92%
“…Heavy-metal toxicity in soil constitutes a substantial hazard to all living beings in the environment [ 48 , 49 ]. Thus, PGPR-assisted bioremediation is a promising, eco-friendly, and sustainable method for eradicating heavy metals [ 50 ]. PGPR strains with heavy-metal resistance belonged to 12 taxa ( Bacillus sp., Bacillus subtilis , Priestia aryabhattai , Priestia megaterium , Pseudomonas flavescens , Pseudomonas reinekei , Pseudomonas sp., Pseudomonas frederiksbergensis , Lelliottia amnigena , Klebsiella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Pb113 and Chitinophaga sp. Zn19 Heavy metal-contaminated soil Two inoculants promote manzanita growth and improve soil zinc pollution remediation efficiency [167] plant growth-promoting rhizobacterium strain MD36 Heavy metal-contaminated soil Strain MD36 effectively improves growth and yield of heavy metal-contaminated soils and bioremediation of HM-contaminated saline soils and water [137] Stenotrophomonas maltophilia Cadmium (Cd)-contaminated soil…”
Section: Pyrene-nickel-contaminated Soilmentioning
confidence: 99%